The Theoretical and Methodological Opportunities Afforded by Guided Play With Young Children - Yu, Yue; Shafto, Patrick; Bonawitz, Elizabeth; Yang, Scott C.-H.; Golinkoff, Roberta M.; Corriveau, Kathleen H.; Hirsh-Pasek, Kathy; Xu, Fei (Frontiers in Psychology, 2018)
For infants and young children, learning takes place all the time and everywhere. How children learn best both in and out of school has been a long-standing topic of debate in education, cognitive development, and cognitive science. Recently, guided play has been proposed as an integrative approach for thinking about learning as a child-led, adult-assisted playful activity. The interactive and dynamic nature of guided play presents theoretical and methodological challenges and opportunities. Drawing upon research from multiple disciplines, we discuss the integration of cutting-edge computational modeling and data science tools to address some of these challenges, and highlight avenues toward an empirically grounded, computationally precise and ecologically valid framework of guided play in early education.